2014
DOI: 10.1002/cncr.28933
|View full text |Cite
|
Sign up to set email alerts
|

Performance characteristics of screening strategies for Lynch syndrome in unselected women with newly diagnosed endometrial cancer who have undergone universal germline mutation testing

Abstract: BACKGROUND: Immunohistochemistry (IHC) for mismatch repair protein expression, microsatellite instability (MSI) testing, tumor morphology, and family history were compared to determine which screening strategy is superior in identifying Lynch syndrome (LS) in unselected women with newly diagnosed endometrial cancer (EC) who have undergone universal germline mutation testing. METHODS: A prospective cohort study was performed that recruited women with newly diagnosed EC. Participants completed a family history a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
103
1
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(119 citation statements)
references
References 28 publications
8
103
1
7
Order By: Relevance
“…Another study documented that 21% of IHCdeficient EMC tumors were MSS by the MSI PCR assay. 12 However, a recent study by McConechy et al 13 showed 93% concordance between the two methods, with 4% MSI-H EMCs missed by IHC, yet only 1% of IHC-deficient EMCs were missed by the MSI assay. Furthermore, the correlation of MSI status with pathologic features of EMCs is also controversial.…”
mentioning
confidence: 97%
“…Another study documented that 21% of IHCdeficient EMC tumors were MSS by the MSI PCR assay. 12 However, a recent study by McConechy et al 13 showed 93% concordance between the two methods, with 4% MSI-H EMCs missed by IHC, yet only 1% of IHC-deficient EMCs were missed by the MSI assay. Furthermore, the correlation of MSI status with pathologic features of EMCs is also controversial.…”
mentioning
confidence: 97%
“…Clinicians have been overlooking most of LS cases accounting for 2-6% of EC patients (Hampel et al 2006;Ferguson et al 2014). To efficiently identify LS in all EC patients and to provide them with appropriate surveillance, we seek a sensible screening strategy for clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The first problem is its costeffectiveness. Considering the fact that LS accounts for 2-6% of all EC patients (Hampel et al 2006;Ferguson et al 2014), opinions on the cost-effectiveness of US are divided. In a comparative study using a simulation model of several LS screening strategies, the strategy that adds an IHC assessment for EC patients who have at least one firstdegree relative with LS-associated cancer has better costeffectiveness than US (Kwon et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations